The bisphosphonate acute phase response: rapid and copious production of proinflammatory cytokines by peripheral blood γδ T cells in response to aminobisphosphonates is inhibited by statins - Hewitt, R E (Blackwell Science Inc, 2005)
The bisphosphonates are a novel class of drug that have been registered for various clinical applications worldwide. Bisphosphonates, and in particular the aminobisphosphonates (nBPs), are known to have a number of side-effects including a rise in body temperature and accompanying flu-like symptoms that resemble a typical acute phase response. The mechanism for this response has been partially elucidated and appears to be associated with the release of tumour necrosis factor (TNF)α and interleukin (IL)6, although the effector cells that release these cytokines and the mechanism of action remain enigmatic. Here, we show that the nBP-induced acute phase response differs from the typical acute phase response in that CD14(+) cells such as monocytes and macrophages are not the primary cytokine producing cells. We show that by inhibiting the mevalonate pathway, nBPs induce rapid and copious production of TNFα and IL6 by peripheral blood γδ T cells. Prior treatment with statins, which inhibit 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase, blocks nBP-induced production of these proinflammatory cytokines by γδ T cells and may offer a means of avoiding the associated acute phase response. In addition, our findings provide a further mechanism for the anti-inflammatory effects attributed to inhibitors of HMG CoA reductase.